Factors Causing Delay of Access to Tuberculosis Diagnosis Among New, Active Tuberculosis Patients: A Prospective Cohort Study. (January 2014) - Shu, Wen; Chen, Wei; Zhu, Shiyu; Hou, Yongchun; Mei, Jian; Bai, Liqiong; Xu, Weiguo; Zhou, Lin; Nie, Shaofa; Cheng, Shiming; Xu, Yihua
Few studies have examined, in a prospective cohort study, factors causing delay of access to tuberculosis (TB) diagnosis among new, active TB patients. A prospective cohort study (2009-2011) was carried out among 408 889 Chinese. Data on known/potential influencing factors were obtained from baseline questionnaires. We used stepwise logistic regression models to analyze the association between several known/potential influencing factors and diagnosis delay, assessed the current situation, and explored determinants of diagnosis delay. During follow-up and final visits, 202 new, active TB patients were found. Median patient delay was 5.4 (quartile 2.7-26) weeks, health system delay was 0 (quartile 0-1.6) weeks, and diagnosis delay was 9.9 (quartile 3.1-28.1) weeks. The influencing factors on patient delay were age and duration of symptoms. Smoking and sputum smear status were influencing factors for health system delay, and duration of symptoms was one of the factors for diagnosis delay. These findings provide information on the current situation of diagnosis delay and evidence for specific strategy development for TB control in China.